Technological change and labor market integration - Elisabeth Bublitz; Michael Wyrwich (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2018)
Could the industrialization reduce social inequalities? We use the rise of office employment in the early 20th century as a historical experiment to study the effect of technological change on labor market access for vulnerable groups. In regions with industries that were strongly connected to the modern office, we find a higher regional labor force participation of disabled people which is explained by better access to the job market for people with physical impairments due to the new office technology. The beneficial employment effect is not distributed equally across gender but is restricted to disabled men. The composition of the workforce in the new white-collar jobs shows no significant differences, implying that vulnerable groups benefitted in similar proportions to workers without health issues. In sum, the second industrialization started to lower labor market entry barriers which gives proof of a market-based leverage effect to foster social inclusiveness.
Keywords: J14; J22; J23; O33; 330; Technological change; labor demand; disability; social inequality